STUDI MANFAAT INOVASI PELAYANAN OBAT DENGAN KOPI TB (KOTAK PENGINGAT MINUM OBAT TB) DI PUSKESMAS BANJARMASIN INDAH KOTA BANJARMASIN - Muhammad Ary Aprian Noor; Lessyana Yulita; Valentina Meta Srikartika (Jurnal Insan Farmasi Indonesia, 2021)
TB (Tuberculosis) is an infectious disease caused by Mycobacterium tuberculosa. Treatment of patiens with regular administration of drugs is done for six months to get healed. The cause of TB treatment failure is the patient forgets to take medication which results in dropping out. Drug service using KOPI TB is a method of TB drugs administration with reminder box to remind patient to take TB medicines that are taken home. This study aims to determine the benefits of innovative drug services using KOPI TB. This research is a quantitative descriptive with prospective data collection using 13 TB patient treatment data in year 2018. The results of this study indicate that there was an increase in the patient cure rate which is 93%, while the rate before innovation was only 86%. The use of KOPI TB also increases the efficiency of TB drugs which the need for TB patient is 13 boxes, while the drugs used was only 12 boxes which is saving 1 box of TB drugs. The conclusion of this study is the innovation of drug services using KOPI TB increases the cure rate of patients and the efficiency of the number of TB drugs used in the Puskesmas.